T - Solution Sdn Bhd / Mohammad Fiqrrie Hatta Ismail ... [et al.] - Ismail, Mohammad Fiqrrie Hatta; Zainal, Zamil Azhar; Abu Adam, Muhammad Shafarin; Mokhtar, Mohd Nazrol; Buliami, Mohd Shaimpor Nizam (Faculty of Architecture, Planning and Surveying, 2005)
The type of business we choose is manufacturing. We found that the nowadays business world is very competitive. So we need something new to introduce. Something that is very special and unique. We study and develop new technology that can be very useful to everyone. As a result, we came out with T Solution to introduce the adjustable toilet bowl. We manufacture, build and sell Adjustable toilet bowl.